Pengaruh Persepsi Individu, Pengetahuan Akutansi dan Pertimbangan Pasar Kerja Terhadap Pemilihan Karir Mahasiswa Akuntansi sebagai Akuntan Publik - Azmy, Rafida; Farizka Susandra; Yoyok Priyo Hutomo (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to reveal the factors that influence accounting students' career choices to become public accountants in the increasingly competitive job market, but public accountants in Indonesia are still relatively low, this shows that opportunities and challenges coexist. This study involved accounting students of the 2021 intake at four universities in the Bogor City and Regency Areas, namely Djuanda University, Ibn Khaldun University, Nusa Bangsa University and Pakuan University with quantitative methods. The sampling technique used a non-probability sampling technique, namely purposive sampling, which is a non-random sampling and has certain criteria, namely 100 respondents with data analysis using the assistance of the Smart Partial Least Squares (PLS) 3.0 computer program, a technique included in Structural Equation Modeling (SEM). The results of the study showed that individual perceptions did not have a significant effect on accounting students' career choices as public accountants. Meanwhile, accounting knowledge and job market considerations had a significant effect on accounting students' career choices as public accountants.